Functional interchangeability of TFIIIB components from yeast and human cells in vitro. - Teichmann, M (1997)
In eukaryotes, TFIIIB is required for proper initiation by RNA polymerase III. In the yeast Saccharomyces cerevisiae a single form of TFIIIB (gammaTFIIIB) is sufficient for transcription of all pol III genes, whereas in extracts derived from human cells two different hTFIIIB complexes exist which we have previously designated as hTFIIIB-alpha and hTFIIIB-beta. Human TFIIIB-alpha is a TBP-free entity and must be complemented by TBP for transcription of pol III genes driven by gene external promoters, whereas hTFIIIB-beta is a TBP-TAF complex which governs transcription from internal pol III promoters. We show that hTFIIIB-beta cannot be replaced by yeast TFIIIB for transcription of tRNA genes, but that the B" component of gammaTFIIIB can substitute for hTFIIIB-alpha activity in transcription of the human U6 gene. Moreover, hTFIIIB-alpha can be chromatographically divided into activities which are functionally related to gammaTFIIIE and recombinant yB"90, suggesting that hTFIIIB-alpha is a human homolog of yeast TFIIIB". In addition, we show that yeast TBP can only be exchanged against human TBP for in vitro transcription of the human and yeast U6 gene but virtually not for that of the yeast tRNA4Sup gene. This deficiency can be counteracted by a mutant of human TBP (R231K) which is able to replace yeast TBP for transcription of yeast tRNA genes in vitro.